Assistance in the Preparation of a Teaching Module for the Strengthening Project of the Pancasila Student Profile (P5) for Elementary Madrasa Teachers in Semarang City - Farda, Ummu Jauharin; Putri, Linda Indiyarti; Imron, Ali; Nida, Afika Khoirun; Septian, Yulia Ayu (LP2M of Institute for Research and Community Services - UIN Walisongo, 2023)
This mentorship activity aimed to enhance the knowledge, understanding, and skills of Madrasah Ibtidaiyah teachers in developing a relevant and applicable teaching module for the strengthening project of the Pancasila student profile (P5) while also improving their self-confidence and collaborative capacity. The Participatory Action Research method was employed, and the mentorship was conducted in three steps: preparation, implementation, and evaluation. The service team completed a preliminary analysis to identify the teachers' needs through interviews, observations, and documentation to ensure effective mentoring. The training results demonstrated a significant increase in participants' knowledge after participating in the P5 teaching module development mentorship. It was evidenced by the survey responses, in which 66.7% of the participants had an improved understanding of the Merdeka Curriculum material and the implementation of P5 through the teaching module.